Brain plasticity in response to artistic and non-artistic training aimed at promoting creativity: How can we enhance creativity and capture the process in neuroscience? - Arkhipova, Anna; Hok, Pavel; Janata, Petr; Hluštík, Petr (Frontiers in Human Neuroscience, 2026)
Creativity has been consensually defined as an ability to produce novel and original ideas/works, a definition shared both by the general public and among scholars. Since creativity is one of the most important and unique cognitive constructs seen in human beings, ways to enhance creativity have fascinated researchers across a broad range of human knowledge domains - from the arts and the humanities to science and technology. The functional process of creativity has been actively discussed not only in psychology, but also in neuroscience, where research is uncovering its neural correlates. A great amount of neuroimaging research has focused on describing anatomical and functional adaptations in the brain following various types of cognitive learning and training, e.g., classes of visual art or music composition, courses of drawing, calligraphy or playing musical instruments. A consistent underlying mechanism of domain-specific creativity has not yet been revealed due to difficulties in defining creativity or due to lack of generalizability across different modalities. On the other hand, recent studies suggest that there is a relationship between domain-general creativity and functional connectivity in particular brain networks. In this review, we discuss whether there is evidence for brain plasticity induced by training in creativity and associated behavioral changes, as well as whether the observed brain changes are consistent with the studies of neurobiological underpinnings of creativity and the changes induced by cognitive training.